2005
DOI: 10.1111/j.1463-1318.2005.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

How has the ‘two‐week wait’ rule affected the presentation of colorectal cancer?

Abstract: Patients referred to the fast-track clinic were seen quicker than those referred by standard letter, but they tended to have more advanced disease. The fast-track referral criteria were fulfilled by most patients with cancer (whether or not they were referred to the fast track clinic), confirming their validity. After detailed interview in the clinic, a quarter of fast-track referrals were found not to satisfy referral criteria, suggesting that prioritization in primary care could be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 8 publications
8
83
1
Order By: Relevance
“…There were seventeen case series that involved 38-3119 patients, two rcts that included 478 and 791 patients, and one case-control study that included 177 cases and 162 controls 4,7,[15][16][17][18][19][20][21][22][23][24][25][26][31][32][33][34][35][36] . The update of the literature search identified 823 citations in which patient outcomes related to diagnostic assessment units were described for colorectal cancer in four studies [27][28][29][30] , head-and-neck cancer in two studies 37,38 , lung cancer in two studies 39,40 , gynecologic cancers in three studies [41][42][43] , neurologic cancers in one study 44 , lymph node cancers in one study 45 , and upper gastrointestinal cancers in one study 46 . Study designs included one small rct (88 patients), seven prospective cohort studies (359-3637 patients), and six retrospective studies (69-930 patients) [27][28][29][30][37][38][39][40][41][42]…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were seventeen case series that involved 38-3119 patients, two rcts that included 478 and 791 patients, and one case-control study that included 177 cases and 162 controls 4,7,[15][16][17][18][19][20][21][22][23][24][25][26][31][32][33][34][35][36] . The update of the literature search identified 823 citations in which patient outcomes related to diagnostic assessment units were described for colorectal cancer in four studies [27][28][29][30] , head-and-neck cancer in two studies 37,38 , lung cancer in two studies 39,40 , gynecologic cancers in three studies [41][42][43] , neurologic cancers in one study 44 , lymph node cancers in one study 45 , and upper gastrointestinal cancers in one study 46 . Study designs included one small rct (88 patients), seven prospective cohort studies (359-3637 patients), and six retrospective studies (69-930 patients) [27][28][29][30][37][38][39][40][41][42]…”
Section: Search Resultsmentioning
confidence: 99%
“…The update of the literature search identified 823 citations in which patient outcomes related to diagnostic assessment units were described for colorectal cancer in four studies [27][28][29][30] , head-and-neck cancer in two studies 37,38 , lung cancer in two studies 39,40 , gynecologic cancers in three studies [41][42][43] , neurologic cancers in one study 44 , lymph node cancers in one study 45 , and upper gastrointestinal cancers in one study 46 . Study designs included one small rct (88 patients), seven prospective cohort studies (359-3637 patients), and six retrospective studies (69-930 patients) [27][28][29][30][37][38][39][40][41][42][43][44][45][46] . Elements of the Downs and Black quality assessment scale for observational studies 14 were used to assess the quality of relevant studies included in the updated review.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thorne et al (17) after checking the information from several papers, demonstrated that only 10.3% of those patients referred following the 2 weeks pathway for a rapid diagnosis of colorectal cancer ended up being diagnosed with cancer, assuming that all entries to the FTDP were correct. This and other studies (18,19) show the poor effectiveness of identifying cancer by using the admission criteria to the diagnostic pathway. This is possibly due to the wrong identification of patients at risk and the unspecific symptoms of CRC.…”
Section: Discussionmentioning
confidence: 99%